Palynology of species of Anthemideae, Eupatorieae, Inuleae, Mutiseae and Senecianeae tribes occurring in the region of Campos Gerais, Paraná State, Brazil - Stanski, Carin; Moro, Rosemeri Segecin; Nogueira, Melissa Koch Fernandes de Souza; Kuniyoshi, Yoshiko Saito; Luz, Cynthia Fernandes Pinto da (Iheringia, Série Botânica., 2019)
We analyzed the pollen morphology of ten species belonging to nine genera of the Asteraceae family, with one species belonging to the Anthemideaetribe (Matricaria chamomilla L.), three belonging to the Eupatorieae [Chromolaena laevigata(Lam.) R. M. King & H. Rob., Mikania micrantha Kunth and Vittetia orbiculata(DC.) R.M.King & H.Rob.], two to the Inuleae (Achillea millefolium L. and Gnaphalium purpureum L.), two to the Mutiseae [Chaptalia integerrima (Vell.) Burkart and Chaptalia graminifolia (Dusén ex Malme) Cabrera], and two species belonging to the Senecioneae tribe [Emilia sonchifolia (L.) DC. and Senecio brasiliensis (Spreng.) Less.]. We used acetolysis to carry out the palynological analysis and pollen grains were studied under light and scanning electron microscopy. The tribes were considered eurypalynous, whose morphological detail allowed the subdivision of species in four groups related to pollen types Anthemis, Eupatorium, Centaurea and Senecio, previously defined in the literature.